Desenvolvimento de uma interface em SIG para suporte ao dimensionamento hidráulico de sistemas de abastecimento de água - Tibúrcio, Eulimar Cunha (2006)
The studies in water resources are models that need data gotten in the maps or research of field. Recently, these information are being added directly in Geographic Information System (GIS) due to the technological advances developed by these systems and to the continuous improvements in digital land model. Currently, efforts have been carried through to develop interfaces in GIS that give support to the work of designers of systems of water supply and, also, evidence it existence of works with hydraulical models allies the GIS. In view of the advances in technology of GIS software, this research it intends to show the viability of the use of GIS applied to the hydraulical sizing of systems of water supply under pressure through the development and application of a connected interface to the ArcMap that uses routines of hydraulical simulator EPANET, allowing, thus, the communication between these two technologies. This interface has as importance the fact to have been constructed with ArcObjects (same platform of development of the family of applications ArcGIS Desktop of the Environmental Systems Research Institute - ESRI); it has as characteristic an easy interaction to sketch hydraulical components through coordinates, allowing, thus, an approach of a model in analysis of a real situation, sizing of components of the system, to supply related information to the operation of the system, to select options of hydraulical simulation, to load the layout of the system in the area of work of the EPANET, to visualize the description-base of the system, to show the report of the last simulation, to visualize hydraulical data of the components each simulation, to modify hydraulical components, to move components for appropriate coordinates, among others; it has as objective to facilitate the activities of the designer of system of water distribution, giving, therefore, continuity to the study of hydraulical models allies the Geo-processing tools; it has, at last, the possibility of continuously being improved to take care of to the new requirements of the designer of nets of water supply.